2017
DOI: 10.1080/02670836.2017.1343263
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hydrostatic extrusion process on the microstructure and texture of polycrystalline nickel

Abstract: The evolution of the microstructure and texture of polycrystalline nickel, from its initial state to that after a hydrostatic extrusion process to total true strains of 0.5, 1.18, 1.62 and 2.2, were examined. Investigation of the microstructure revealed that the grain size was reduced from ∼32 µm to ∼200 nm. The local texture transformation and major boundary misorientation angles were discussed based on electron backscattered diffraction results, while XRD was used to give a qualitative and quantitative descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In order to determine the influence of initial texture on the formation of the deformation texture, it was necessary to analyse the texture of the polycrystalline aluminium before the HE process. Other studies on polycrystalline alloys after HE revealed the formation of double fibre texture [23,31,32] with different volume fractions of the 111 and 001 components. In order to perform a more detailed analysis, quantitative calculations of texture components were conducted (figure 6).…”
Section: Texturementioning
confidence: 92%
“…In order to determine the influence of initial texture on the formation of the deformation texture, it was necessary to analyse the texture of the polycrystalline aluminium before the HE process. Other studies on polycrystalline alloys after HE revealed the formation of double fibre texture [23,31,32] with different volume fractions of the 111 and 001 components. In order to perform a more detailed analysis, quantitative calculations of texture components were conducted (figure 6).…”
Section: Texturementioning
confidence: 92%
“…{111} < 110 > and {111} < 112 > ) and α-fiber texture (i.e. {111} < 110 > , {112} < 110 > and {001} < 110 > ) [21][22][23][24][25]. The difference is mainly due to the deformation condition, namely the large torque with super high hydrostatic pressure.…”
Section: Microstructure Evolutionmentioning
confidence: 99%
“…But the relationship between the texture structure and elastic modulus under HPT deformation is unclear. Recently, the texture evolution of Mo and other metals in previous literature is mainly based on hot rolling, uniaxial compression, extrusion process and heat treatment [21][22][23][24][25]. There are obvious differences between the microstructure formed by HPT deformation and by the conventional plastic deformation process, which is due to severe continuous shear deformation under extremely high hydrostatic pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrostatic extrusion is optimal for fabricating products experiencing a high strain and possessing a complex shape. This is because the process conditions enable the exertion of a uniform pressure on the product, accompanied by a low friction between the product and the container with the help of a surrounding fluidlike grease [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%